Pembuatan Aplikasi Reservasi Pasien Covid-19 di Rumah Sakit Muhammadiyah Bandung - Surya Dhama, Ananda Meilana; Sonia, Dina; Agustin, Cahyadi (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
The results of field work practice at the Bandung Muhammadiyah Hospital, the authors pay attention to several problems, namely when registering Covid-19 patients, during registration, Covid-19 patients will come to the hospital and wait and even queue to register, this process can cause the spread of the virus to people in the hospital. Based on the background of these problems, the author chose to make an application, with the argument that the majority of Indonesian people have smartphones. By creating an online reservation application, patients do not need to wait in the hospital first so that the risk of covid transmission is reduced, Then the hospital can prepare for the arrival of Covid patients so that visitors do not need to worry and in the end the Covid patient registration activity can run by minimizing the occurrence of transmission. Research methodology is a scientific way to obtain data with specific purposes and uses (Sugiyono, 2016). For making this application, the author uses research and development methods. Research and Development (R&D) is a research method used to produce certain products and test the effectiveness of these products. The results obtained from making this application are the development stage and show changes in registering Covid-19 patients. What initially required patients to come to the hospital to register, became online (online), namely electronic devices connected to the internet network. So it can be done through this application. The overall application deployment is a mix of software and hardware. This application is able to make reservations (reservations) for patients who are confirmed to be COVID-19 in online. Keywords : Registering, Covid-19, Hospital, Application, Reservation